Numerical Modelling of Hydrodynamic Changes Induced by a Jetty Extension: the Case of Ria de Aveiro (Portugal) - Dias, J. M. (2011)
Tidally induced currents in estuarine flows are usually modulated by the tidal regime and respond differently to changes imposed to its natural propagation due to geomorphologic alterations. Some of these changes are due to the implementation of heavy engineering works, most of the times imposed by navigation needs associated with harbours growth. The main purpose of this study is to evaluate the hydrodynamic response of Ria de Aveiro to an alteration on the present geometry of its inlet, which was artificially delimited in 1808 through the construction of two jetties. In order to provide access to deeper draft vessels to the Aveiro harbour, its Administration intends to create better conditions for navigation through the extension by 200 m of the north jetty. A bidimensional hydrodynamic model SIMSYS2D was used in this study to simulate two distinct situations: the actual Ria de Aveiro configuration (2009), which is used as reference, and other including the future inlet configuration with the jetty extension. Several simulations were performed, using both bathymetries and considering extreme tidal conditions as forcing on the model oceanic open boundary. The tidal prism at the lagoon mouth and at the main lagoon channels was determined. Values of sea surface elevation and horizontal current velocity were comparatively analyzed as well as harmonic analysis results. The results for the projected inlet increase comparatively to those for the present configuration, although the differences found are not significant for most of the cases analyzed. More studies should be performed in order to clarify the long term impact of these works on the lagoon hydrodynamics.